RELIGIOUS ENVIRONMENT AND THE SPREAD OF ISLAM IN MAVERANNAHR IN THE WORKS OF HERMAN VÁMBÉRY - Kabulov Rustam Jumaniyozovich (International Journal of Literature and Language Studies, 2026)
This article analyzes the religious processes in Maverannahr, the introduction of Islam during the period of the Arab conquest, the attitude of the local population toward the new religion, and the formation of the religious environment on the basis of the work History of Bukhara or Transoxiana by the nineteenth-century orientalist and traveler Herman Vámbéry. The author's information is studied through historical-comparative and source-critical methods, and the spread of Islam is assessed not only as a religious phenomenon but also as a political and cultural process. The results of the study demonstrate that Islamization in Maverannahr was a complex historical process that lasted for a long period.